NLRP3 Inflammasome Activation Is Involved in Geniposide-Induced Hepatotoxicity - Yixuan Liu; Baoyue Liu; Mingzhu Shi; Tianxiang Ye; Huifang Li (Mediators of Inflammation)
Conclusions: Our findings collectively elucidate that geniposide induces hepatotoxicity by triggering NLRP3 inflammasome signaling. Inhibition of the inflammasome presents a promising novel therapeutic target for mitigating geniposide-induced hepatotoxicity.